KESENJANGAN SOSIAL-EKONOMI PASCA PANDEMI COVID-19 : ANALISIS KRITIS TERHADAP PENYEBAB DAN DAMPAKNYA PADA MASYARAKAT DI INDONESIA - Fathur Al Araafi; Muhammad Sadam; Keisha Nahda Tsabitah; Radhita Rasya Anindya; Fatkhuri Fatkhuri (Jurnal Bina Bangsa Ekonomika, 2024)
The COVID-19 pandemic, first detected in Wuhan, China, in late 2019 created a challenge to public health unprecedented in modern history and had a major impact on public health. In addition to the direct impact on physical health, COVID-19 also has a negative impact on economic and social aspects. The phenomenon of social inequality in the impact of the COVID-19 pandemic is very visible and has exacerbated pre-existing aspects of social and economic inequality. Therefore, this study was conducted to further analyze the causes and impacts of the COVID-19 pandemic on socio-economic inequality in society. This research uses qualitative rules through data collection with a descriptive-qualitative analysis approach. The results of the study found that the causes of socio-economic inequality after the COVID-19 pandemic were bloated health financing, massive wage reductions and layoffs (Termination of Employment) that had a significant impact on the economic and social sectors. This research is expected to contribute to the development of political science studies through critical analysis related to the dynamics and appropriate public policies in overcoming socio-economic gaps after the Covid-19 pandemic in Indonesia